Sweet Thunder [large type] - Doig, Ivan (Thorndike Press, 2013)
In the winter of 1920, a bequest draws Morrie Morgan back to Butte, Montana, with his bride, Grace. But the mansion bestowed by a former boss proves to be less windfall than money pit. And the town, with its polyglot army of miners struggling against the ruthless Anaconda Copper Mining Company, seems on the verge of implosion. These twin dilemmas catapult Morrie into his new career as editorialist for the Thunder, the fledgling union newspaper.